Three decades of changes in the construction of La Plata horticultural territory (Buenos Aires province, Argentina). Dialogue between the perceptions of local actors and information derived from remote sensing (Huellas, 2025)
Productive peri-urban areas are extremely complex territories, with a diversity of actors and interests. Various authors investigated the peri-urban area of ​​La Plata and observed territorial planning deficiencies. In the present work, through semi-structured interviews and participant observation, the perception of a diversity of actors on the territorial transformations of the horticultural belt of La Plata city (prov. of Buenos Aires, Argentina) and the public policies implemented were investigated. Likewise, these results were put into dialogue with those of an analysis previously carried out by the research group, based on satellite images. Coinciding with the analysis of satellite images, the interviewees clearly identified territorial transformations, enriching the results with information on the possible causes and on the territorial actors and existing power relations.
Keywords: Territorial planning; Horticultural periurban; Territorial transformations; Public policies; Social perception